2013
DOI: 10.1080/13811118.2013.805647
|View full text |Cite
|
Sign up to set email alerts
|

Affective Instability Prior to and after Thoughts about Self-Injury in Individuals With and At-Risk of Psychosis: A Mobile Phone Based Study

Abstract: It has been proposed that affective instability may be associated with thoughts about self-injury. The aim of this study was to test the hypotheses that instability in feelings of depression, but not anxiety, guilt, or hostility, would predict greater concurrent and subsequent thoughts about self-injury. Thirty-six individuals with psychosis completed questions on touch-screen mobile phones at semi-random times each day for one week. The instability of depression predicted greater concurrent and subsequent lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Seven interventions were delivered using smartphones or other mobile platforms. Many interventions relied on automated prompting of participants to report symptoms at specific times during the day including mood, psychological state, or positive and negative affect (Ainsworth et al, 2013; Ben-Zeev et al, 2012; Bopp et al, 2010; Depp et al, 2012; Faurholt-Jepsen et al, 2014; Palmier-Claus et al, 2012; Palmier-Claus, Ainsworth, et al, 2013; Palmier-Claus, Rogers, et al, 2013; Palmier-Claus et al, 2014), except for one smartphone program designed to continuously collect data on movement, location, physical activity, and social interactions in combination with question prompts (Grünerbl et al, 2012). There was one computer-based intervention for recording mood and measures of medications, sleep, life events, menstrual data, and weight (Bauer et al, 2004), and one online intervention for daily rating of mood, anxiety, and depression (Lieberman et al, 2010; Lieberman et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Seven interventions were delivered using smartphones or other mobile platforms. Many interventions relied on automated prompting of participants to report symptoms at specific times during the day including mood, psychological state, or positive and negative affect (Ainsworth et al, 2013; Ben-Zeev et al, 2012; Bopp et al, 2010; Depp et al, 2012; Faurholt-Jepsen et al, 2014; Palmier-Claus et al, 2012; Palmier-Claus, Ainsworth, et al, 2013; Palmier-Claus, Rogers, et al, 2013; Palmier-Claus et al, 2014), except for one smartphone program designed to continuously collect data on movement, location, physical activity, and social interactions in combination with question prompts (Grünerbl et al, 2012). There was one computer-based intervention for recording mood and measures of medications, sleep, life events, menstrual data, and weight (Bauer et al, 2004), and one online intervention for daily rating of mood, anxiety, and depression (Lieberman et al, 2010; Lieberman et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Although other predictors of adherence were examined (age, gender, cognition, negative symptoms, and persecutory delusions), none were found to have a significant effect. Two studies also found significant predictors of dropout: severity of symptoms [ 39 ], younger age, and male gender [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the original validation study, the item “I have had thoughts about harming myself” was included in the depression momentary assessment scale. For the purpose of this analysis and other papers (Palmier‐Claus, Ainsworth, et al., ), this item was included as a separate scale to measure SITs. Logistic regression suggested that this momentary assessment item was a strong predictor of suicidality measures on the Calgary Depression Scale (Addington, Addington, & Schissel, ; OR = 2.40, SE = .790, p = .008), attesting to convergent validity of this item.…”
Section: Methodsmentioning
confidence: 99%